2020
DOI: 10.1111/evj.13212
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography characteristics of equine paranasal sinus cysts

Abstract: Background Computed tomography (CT) is commonly used to investigate equine paranasal sinus disease, however, only limited information is available in the literature about the detailed CT appearance of equine paranasal sinus cysts. Objectives To investigate if paranasal sinus cysts have specific characteristics in CT images that allow differentiation from other sinus diseases. Study design Retrospective observational study. Methods Evaluation and comparison of CT studies of eight horses with surgically and/or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
14
2
Order By: Relevance
“…Paranasal sinus cysts are commonly unilateral; bilateral disease is only rarely reported. In a recent study (19) investigating CT characteristics of paranasal sinus cysts, seven of eight cysts demonstrated a soft tissue to mineral attenuating wall; this finding was not detected in this case series of sino-nasal obstruction. Paranasal sinus cysts are typically expansile lesions; therefore, bone distortion is a common finding.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Paranasal sinus cysts are commonly unilateral; bilateral disease is only rarely reported. In a recent study (19) investigating CT characteristics of paranasal sinus cysts, seven of eight cysts demonstrated a soft tissue to mineral attenuating wall; this finding was not detected in this case series of sino-nasal obstruction. Paranasal sinus cysts are typically expansile lesions; therefore, bone distortion is a common finding.…”
Section: Discussioncontrasting
confidence: 63%
“…In the patient with secondary infection following trephination, the recorded values did not differ from those measured in sinus compartments filled with clear fluid. A recent study demonstrated that HU measurements are not reliable to differentiate between cyst fluid and sinus mucus or exudate ( 19 ). Recorded HU were in the same range as those measured in the present study excluding HU as a means of differentiating between primary sinusitis and the idiopathic pathology in this case series.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplanar diagnostic imaging (CT, magnetic resonance imaging) provides detailed information in assessing sinus disease in horses for a more accurate preoperative diagnosis to guide surgical planning (Easley & Freeman, 2013;Ostrowska et al, 2019;Textor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multiplanar diagnostic imaging (CT, magnetic resonance imaging) provides detailed information in assessing sinus disease in horses for a more accurate preoperative diagnosis to guide surgical planning (Easley & Freeman, 2013 ; Ostrowska et al., 2019 ; Textor et al., 2012 ). Patients that experience recurrence or lack of resolution of clinical signs following sinusotomy are good candidates for CT examination if the cause of recurrence is not apparent (Barakzai & Dixon, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Henninger et al provided detailed CT descriptions regarding the most common features of sinusitis and alveolitis [32]. Diagnosis and surgical treatment of sinonasal cysts have been described [33][34][35]. Solano et al depicted CT images of empyema, even though endoscopy is the preferred method for the diagnosis process of guttural pouches [24].…”
Section: Clinical Applicationsmentioning
confidence: 99%